Enhancing jump performance with handheld loading - McKenzie, C.; Brughelli, M.; Gamble, P.; Whatman, C. (Strength and Conditioning Journal, 2014)
The concept of using handheld loading during a standing long jump dates back almost 3,000 years to ancient greece. This may have been one of the earliest attempts to passively enhance athletic performance. Despite numerous limitations in the more recent literature, researchers have reported acute enhancements in horizontal jumping distance. However, the long-term effects of handheld loading have never been investigated. The purposes of this review are to provide (a) a comprehensive review of literature on the acute effects of handheld loading on horizontal jumping performance, (b) direction for future research, and (c) practical recommendations for strength and conditioning.